In vitro hydrolysis of Bacillus thuringiensis Cry1Ac toxin by gut proteases of Nilaparvata lugens (Stål) and binding assays of Cry1Ac toxin with brush border membrane of N. lugens midgut. Issue 5 (4th May 2018) - Shao, Ensi; Chen, Chen; Chen, Hanze; Liu, Sijun; Lin, Li; Wang, Yaomin; Guan, Xiong; Huang, Zhipeng
ABSTRACT: Bacillus thuringiensis (Bt) and transgenic crops carrying cry genes are widely used in the management of lepidopteran and coleopteran pests. However, almost none of the Cry toxins have insecticidal properties against sap-sucking insects, such as planthoppers, leafhoppers and aphids. To understand the low insecticidal activity of Cry1Ac toxin on sap-sucking insects, we investigated two critical steps in the Bt-intoxication cascade: the proteolytic processing of Cry1Ac toxin by gut proteases, and the binding of Cry1Ac to brush border membrane vesicles (BBMV) of Nilaparvata lugens . Proteolytic processing of Cry1Ac protoxin by N. lugens gut proteases resulted in an ∼65 kDa product, similar to the expected size of the trypsin-activated Cry1Ac toxin. In addition, activation of cysteine proteases in N. lugens gut increased the efficiency of proteolytic activities in the processing of Cry1Ac. However, feeding N. lugens nymphs with either Cry1Ac protoxin or trypsin-activated Cry1Ac toxin resulted in low mortalities. The LC50 of Cry1Ac protoxin and trypsin-activated Cry1Ac was 198.92 and 450.18 μg/mL, respectively. In vitro binding analysis of BBMV with the pre-activated Cry1Ac showed that Cry1Ac toxin could specifically bind to the BBMV. However, binding competition with 500-fold molar excess GalNAc ( N -acetyl-d -galactosamine) suggested that the binding was not mediated by GalNAc-like glycoproteins. These results indicate that Cry1Ac toxin could be successfully processed by the treatment of N. lugens gut proteases. However, the binding of Cry1Ac toxin to the midgut brush border membrane was not mediated by GalNAc-like glycoprotein. This may be responsible for the low susceptibility of N. lugens to Cry1Ac.